1993
DOI: 10.1127/ejm/5/1/0133
|View full text |Cite
|
Sign up to set email alerts
|

The effect of P2O5 on the viscosity of haplogranitic liquid

Abstract: : The effect of P2O5 on the viscosity of a haplogranitic (K2O-Na2O-AhO3-SiO2) liquid has been determined at 1 atm pressure in the temperature interval of 700 -1650°C. Viscosity measurements of a haplogranite, haplogranite + 5.1 wt.% P2O5 and haplogranite + 9.5 wt.% P2O5 have been performed using the concentric cylinder and micropenetration methods.The viscosity of haplogranite liquid decreases with the addition of P2O5 at all temperatures investigated. The viscosity decrease is nonlinear, with the strongest de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 23 publications
(26 reference statements)
2
55
0
2
Order By: Relevance
“…This mechanism explains the decrease of viscosity caused by F in silicate melts DINGWELL, 1989), and it might also be responsible for the effect of F on diffusion coefficients. An extensive discussion of the physical properties of F-containing melts and their possible relationship to melt structure can be found in the paper by DINGWELL (1985).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism explains the decrease of viscosity caused by F in silicate melts DINGWELL, 1989), and it might also be responsible for the effect of F on diffusion coefficients. An extensive discussion of the physical properties of F-containing melts and their possible relationship to melt structure can be found in the paper by DINGWELL (1985).…”
Section: Applicationsmentioning
confidence: 99%
“…Concentrations of several wt.% are reported in high-fluorine rhyolites (CONGDON and NASH, 1988) and in ongonites ( KOVALENKO, 1973). Similar to water, the presence of F strongly reduces the viscosity of silicate melts ( DINGWELL et al, 1985;DINGWELL, 1989) and increases diffusion coefficients ( DINGWELL, 1985). Even small amounts of F in the order of 1 wt.% will therefore significantly change the transport properties, mobility, and eruption behavior of such magmas.…”
mentioning
confidence: 99%
“…The crucibles were heated in air and, to limit further possible changes in FeZ+/Fe 3+ ratio, the heating Richet and Bottinga (1984a) indicate cooling rates of a few K/s through the glass transition in our experiments. Viscosity measurements on stable liquids were performed in air with the concentric cylinder viscometer described by Dingwell (1989). Measurements on supercooled liquids were also made in air, with a fiber-elongation method, as described by Webb and Dingwell (1990b), and with the creep apparatus described by Neuville and Richet (1991).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This technique yields absolute viscosities and has been checked against the viscosity of NBS 711 glass. It has been demonstrated that, over the range of 109-1011 Pa s, viscosity can be determined with an accuracy of + 0.1 log~o Pa s. Details regarding the theory for the micropenetration technique can be found in Dingwell et al ( 1992Dingwell et al ( , 1993.…”
Section: Viscosity Measurementsmentioning
confidence: 99%
“…The furnace, the setup and the computer interface together with the exact procedure and calibration are described by Dingwell and Virgo (1988) and Dingwell ( 1989aDingwell ( , b, 1990. With this technique a temperature range from 800 ° to 1650 °C and a viscosity range from 10 ° to 105 Pa s can be covered.…”
Section: Viscosity Measurementsmentioning
confidence: 99%